Recrystallized quinolinium ionic liquids for electrochemical analysis - Selvaraj, G. (American Institute of Physics Inc., 2016)
Ionic liquids have received a lot of attention due to their unique properties. In this work the prospect of quinolinium based ionic liquids as electrolyte for dye sensitised solar cell were tested using cyclic voltammetry. The results have shown electron transfer in the ionic liquid without undergoing any permanent chemical changes. Prior to testing, the ionic liquids were purified through recrystallization as electrochemical properties of ionic liquids are highly dependent on the purity of the ionic liquids. This results have shone new light for this work. Â© 2016 Author(s).